SQL Server 2016 database reporting - Snider, Dallas (Packt Publishing, 2017)
"With SQL Server 2016 Reporting Services, users are excited about being able to visualize their data in new, creative ways for use in presentations, analysis, and decision support--even on mobile devices. In this course, users will receive step-by-step instructions on how to create stunning, high-impact reports. The course starts with an introduction to the technologies employed. Next, users are shown how to create a basic report and then how to format it and add features (such as headers and footers) to make it more readable, impressive, and practical. The course teaches how to create drill-down and drill-through reports. Pie charts, gauges. and maps are next on the agenda and the course wraps up with lessons on how to assemble a dashboard on the SQL Server Reporting Services web portal. This course will empower you to overcome any obstacle while creating interactive, visually-appealing reports using SQL Server 2016 Reporting Services."--Resource description page.